Synthesis of metal-polymer nanocomposites - Hasell, Tom (2008)
This thesis details the synthesis and characterisation of novel nanocomposite materials. The unifying theme of all the projects investigated, is the aim to combine metal or metal oxide nanoparticles with polymer systems. In order to investigate the structure of the materials produced, the extensive use of advanced electron microscopy techniques is essential throughout.